Differences between managers' and safety professionals' perceptions of upwards influence attempts within safety practice. (June 2022) - Madigan, Cassandra; Way, Kïrsten A.; Johnstone, Kelly; Capra, Mike
Highlights: Rational persuasion (RP) and legitimating (LGT) were the most frequently used. Pressure and personal appeals were the least frequently used tactics. RP was the most effective tactic; LGT was less effective in influencing managers. Knowledge, interpersonal skills, and experience enabled influence. Organizational culture, leadership styles, and safety beliefs impede influence. Abstract: Introduction: The ability to influence upwards and gain management commitment has been identified as an essential capability for safety professionals, yet little is known about managers' perceptions of their subordinates use and effectiveness of influence tactics. This study utilizes intra-organizational influence theory to explore how safety professionals influence managers who are making important safety decisions. Method: Survey data were collected from managers ( n = 145) on influence tactics used by safety professionals, perceived outcomes, and factors that promote and impede influence. Survey data from a previous study of safety professionals ( n = 385) were used to compare the differences in perceptions between the two groups. Results: Managers perceive that the use of influence tactics provides explanation for safety professionals' effectiveness, with rational persuasion being positively associated with influencing effectiveness, and personal appeals and legitimating being negatively associated with effectiveness. Certain factors (i.e., knowledge, understanding organizational context, interpersonal skills, and experience) were more frequently perceived by managers to enable influence, while others were more frequently reported as barriers (i.e., organizational culture, safety beliefs, and leadership styles of managers). Managers and safety professionals agreed on many of these findings, although safety professionals reported a broader range of tactics as being effective than did managers. Conclusions: This study provides important contributions to understanding the upward influence behavior of safety professionals, and to our knowledge is the first study to report this behavior from the perspective of managers. Practical Applications: These findings may prompt safety professionals to reflect on current tactic usage and associated efficacy from managers' perspectives. Safety professionals should also consider the culture of the organization, safety beliefs, and the leadership style of managers prior to influencing, as these factors may negatively impact influencing outcomes. Developing knowledge and skills in both technical and non-technical domains may enhance the strategic influence of safety professionals.